Impact of a novel community testing pathway for people with suspected COVID-19 in Wales: a cost-minimisation analysis. Issue 8 (16th August 2020) - Currie, Jonny; Adamson, James; Bowden, Bethan; Woolls, Julie; Jones, Rachel; Healy, Brendan; Heyburn, David; Shankar, Ananda Giri; Howe, Robin
Abstract : Objective: To compare National Health Service (NHS) organisations' testing pathways for patients with suspected COVID-19 in the community versus standard hospital testing practices. Perspective: NHS commissioners and services. Methods: During the containment phase of the COVID-19 pandemic we developed a community model pathway for COVID-19 testing in Wales with testing teams undertaking swabbing for COVID-19 in individuals' usual place of residence. We undertook a cost-minimisation analysis comparing the costs to the NHS in Wales of community testing for COVID-19 versus standard hospital testing practices and ambulance conveyancing. We analysed data from patients with suspected COVID-19 between January and February 2020 and applied assumptions of costs from national contractual and reference costs for ambulances, staffing and transportation with market costs at the time of publication. Results: 177 patients with suspected COVID-19 underwent community testing via local NHS organisations between January and February 2020 with a mean age of 46.1 (IQR 27.5–56.3). This was 92% of total patients who were tested for COVID-19 during this period. We estimate, compared with standard hospital testing practices, cash savings in improved productivity for the NHS of £24, 539 during this time period, in addition to further non-monetised benefits for hospital and ambulance flow. Conclusions: Community testing for COVID-19 in Wales is now an established pathway and continues to bring benefits for patients, local healthcare organisations and the NHS. Further application of this model in other settings and to other infectious diseases may herald promising returns.